1966
DOI: 10.1038/icb.1966.60
|View full text |Cite
|
Sign up to set email alerts
|

Effects of X‐irradiation on Antigen Localization in Lymphoid Follicles

Abstract: Summary. Tlic effects of whole hotly X-iiradiation hcltirc or alter tlic iiijcclinn ol '-"•l-fal>('llc Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Nevertheless they confirm the early observations of Jaroslow and Nossal [17] and of Nettesheim and Hanna [18] that rat or mouse FDC with trapped radiolabeled antigens are not destroyed by irradiation up to 18.5 Gy, although even after 4.5 Gy their capacity to hold antigens is gradually impaired. Ingenious experiments by Brown et al [3] indicated that a radiosensitive population of presumptive B lymphocytes in the spleen, possibly in the marginal zone, was needed for localization of aggHGG on FDC.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless they confirm the early observations of Jaroslow and Nossal [17] and of Nettesheim and Hanna [18] that rat or mouse FDC with trapped radiolabeled antigens are not destroyed by irradiation up to 18.5 Gy, although even after 4.5 Gy their capacity to hold antigens is gradually impaired. Ingenious experiments by Brown et al [3] indicated that a radiosensitive population of presumptive B lymphocytes in the spleen, possibly in the marginal zone, was needed for localization of aggHGG on FDC.…”
Section: Discussionsupporting
confidence: 89%
“…This led to the suggestion that FDCs could be candidates in the peripheral replication of the agent and this has been sustained by the immunolocalization of the normal host protein, PrP, which has a pivotal role in scrapie cellular pathogenesis . FDCs are radiationresistant (Jaroslov & Nossal, 1966) and not dependent on a high level of replenishment. Their function includes subserving B cell immunity and hence immunological memory (Koscoe et aI., 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The stroma of follicles is constituted from follicular dendritic cells that can trap and retain antigen (Nossal et al 1964(Nossal et al , 1968Mitchell and Abbot 1965 ;Hoefsmit 1975 ;Chen et al 1978 ; Klaus et al 1980). It has been reported that X-irradiation causes damage to a certain extent to the morphology of follicular dendritic cells and to the capacity of these cells to retain antigen (Jaroslow and Nossal 1966 ;Williams 1966 ;Nettesheim and Hanna 1969). The present study suggests that in spite of such damage, each persisting stroma of follicles damaged by 600 R X-irradiation may retain the capacity to collect circulating B lymphocytes and reform the lymph follicle.…”
Section: Discussionmentioning
confidence: 99%